'We should google that': the dynamics of knowledge-in-interaction in an online student meeting. Issue 2 (3rd April 2022) - Dooly, Melinda; Tudini, Vincenza
ABSTRACT: This paper takes a multimodal conversation analytic approach to explore knowledge-in-interaction in a technology-mediated online environment (Skype videoconference) during a meeting between eight university students studying to become language teachers. The analysis considers the ways in which the student-teachers demonstrate their knowledge or understanding of telecollaborative project-based language learning while taking part in a telecollaborative exchange themselves. Given the growing predominance of online teaching and learning, it is increasingly relevant to have a deep understanding of the ongoing learner interaction that takes place in these environments, particularly considering that interaction can be understood as a trajectory of knowledge building. The study examines how the student-teachers make use of the different technological features of a videoconferencing platform to manage the assigned task, which is to complete a collaborative exam. These features include camera, shared links, parallel text chats and editing tools. Findings imply that the student-teachers sequentially organise their knowledge synthesis and co-construction of pedagogical understanding through technologically-supported mutually coordinated interaction. Although the analysis is contextually bound, the task-focused interaction that is highlighted is relevant to higher education teachers in a variety of contexts, apart from teacher education.